If T: (x, y) → (x – 3, y + 2), then T -1: (x,y) → _____. (x + 3, y + 2) (x + 3, y – 2) (, -) (3x, -2y)<

Question

If T: (x, y) → (x – 3, y + 2), then T -1: (x,y) → _____.

(x + 3, y + 2)
(x + 3, y – 2)
(, -)
(3x, -2y)

in progress 0
Clara 2 weeks 2021-10-11T22:59:31+00:00 1 Answer 0

Answers ( )

    0
    2021-10-11T23:01:22+00:00

    Answer:

    (x + 3, y – 2)

    Step-by-step explanation:

    we know that

    The rule of the transformation T is equal to

    T: pre-image → image

    T: (x, y) → (x’,y’)

    T: (x, y) → (x – 3, y + 2)

    so

    x’=x-3 —-> x=x’+3

    y’=y+2 —-> y=y’-2

    The rule of the inverse of transformation T -1 is equal to

    T-1: image → pre-image

    T-1: (x’, y’) → (x,y)

    T-1: (x’, y’) → (x’+3, y’-2)

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )